2021
DOI: 10.1080/00015458.2021.1883391
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment delays on outcome of acute testicular torsion: a 15-year retrospective study

Abstract: Introduction: Preservation of the testicle is directly associated with the duration of torsion. The aim in this retrospective study was to identify factors that influence pre-and in-hospital times and measure the extent to which these times affect testicle survival. Patients and methods: A retrospective review of 116 patients who underwent exploration for testicular torsion between 2000 and 2015. Patients were divided into orchiectomy and salvaged testicle groups. Times in patient management and clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…Testicular torsion is the cause of pediatric acute scrotum in 10-15% of cases, and in such cases, about 40% of surgical explorations result in an orchiectomy [1][2][3]. To avoid unfavorable outcomes and to ensure the viability of the testis, a diagnosis must be made promptly, ideally within 6 hours [4][5]. It is therefore important to know the classic presentation of testicular torsion which consists of sudden onset unilateral testicular pain which may be accompanied by nausea and/or vomiting [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Testicular torsion is the cause of pediatric acute scrotum in 10-15% of cases, and in such cases, about 40% of surgical explorations result in an orchiectomy [1][2][3]. To avoid unfavorable outcomes and to ensure the viability of the testis, a diagnosis must be made promptly, ideally within 6 hours [4][5]. It is therefore important to know the classic presentation of testicular torsion which consists of sudden onset unilateral testicular pain which may be accompanied by nausea and/or vomiting [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 10 Confirmatory findings demonstrate decreased or lack of blood flow to the affected testicle. While it has been reported that scrotal imaging may contribute to the delay in surgically treating testicular torsion and result in increased orchiectomy rates, 3 , 9 failure to perform this test often leads to misdiagnosis of this urgent condition. 10 …”
Section: Discussionmentioning
confidence: 99%
“…1,3 Patients who have orchiectomies are often hospitalized for longer periods of time which results in higher healthcare costs. 9 Delayed and incorrect diagnosis are the primary reasons for unsalvageable testes. 3 Prompt and accurate diagnosis of testicular torsion is imperative to avert testicular loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients presenting to a primary medical practitioner generally have a longer median pre‐hospital time 16 . Online learning modules and training offer the opportunity to improve the triage and assessment of children with urgent surgical conditions 17 .…”
Section: Discussionmentioning
confidence: 99%